HUBUNGAN KOMUNIKASI VERBAL TUTOR DAN MOTIVASI BELAJAR WARGA UNTUK BELAJAR PROGRAM KESETARAAN SEKOLAH MENENGAH DI SANGGAR KEGIATAN BELAJAR - Munawwarah Ahmad; Hartini Wulandari (Universitas Negeri Medan, 2025)
The aims of this research are; 1) To determine the tutor's verbal communication with residents studying Package C classes X and XI, 2) To determine the learning motivation of residents studying Package C Classes X and XI at the Binjai City SKB. This type of research is descriptive correlational research. The population in this study was 30 students studying package C classes X and XI. The sample for this research was the entire population, namely 30 people using a total sampling technique. Data collection techniques use questionnaires and documentation instruments. The data analysis technique uses the product moment correlation formula, t test and simple linearity. From the research results, it can be concluded that there is a relationship between the tutor's verbal communication and the learning motivation of residents studying package C at SKB Binjai City. This is known from the calculation results obtained by the price rxy > rtable, namely 0.408 > 0.361. So the hypothesis which reads: